Recruitment of ethnic minorities into cancer clinical trials: experience from the front lines - Symonds, R P (Nature Publishing Group, 2012)
Throughout the world there are problems recruiting ethnic minority patients into cancer clinical trials. A major barrier to trial entry may be distrust of research and the medical system. This may be compounded by the regulatory framework governing research with an emphasis on written consent, closed questions and consent documentation, as well as fiscal issues. The Leicester UK experience is that trial accrual is better if British South Asian patients are approached by a senior doctor rather than someone of perceived lesser hierarchical status and a greater partnership between the hospital and General Practitioner may increase trial participation of this particular ethnic minority. In Los Angeles, USA, trial recruitment was improved by a greater utilisation of Hispanic staff and a Spanish language-based education programme. Involvement of community leaders is essential. While adhering to national, legal and ethnical standards, information sheets and consent, it helps if forms can be tailored towards the local ethnic minority population. Written translations are often of limited value in the recruitment of patients with no or limited knowledge of English. In some cultural settings, tape-recorded verbal consent (following approval presentations) may be an acceptable substitute for written consent, and appropriate legislative changes should be considered to facilitate this option. Approaches should be tailored to specific minority populations, taking consideration of their unique characteristics and with input from their community leadership.